Development of Intelligent Operation Platform for GIS Combiner Installation. Issue 1 (June 2021) - Jianjun, Fang; Zhaoqing, Jiang; Yanping, Li; Yang, Han
Abstract: In order to improve the installation efficiency of GIS combined electrical apparatus and reduce the installation cost, the intelligent operation platform for GIS installation is developed in this paper. The platform adopts the concept of functional modular design, can replace the modular manipulator according to the different types of installation, and is easy to disassemble and assemble. The application of accurate installation and one-time positioning platform can effectively reduce the dependence on large lifting equipment such as cranes and scrapers, avoid the occurrence of bumps and damage to insulation during installation, and improve the installation quality of equipment. Effectively prevent equipment from the defects caused by engineering construction, and ensure power grid operation safety.